Answer:
See below for answers and explanations (with attached graph)
Step-by-step explanation:
It helps to transform the equation into vertex form by completing the square because it tells us a lot about the characteristics of the parabola:
[tex]\displaystyle y=-6x^2+12x-8\\\\y=-6\biggr(x^2-2x+\frac{4}{3}\biggr)\\\\y-6\biggr(-\frac{1}{3}\biggr) =-6\biggr(x^2-2x+\frac{4}{3}-\frac{1}{3}\biggr)\\\\y+2=-6(x^2-2x+1)\\\\y+2=-6(x-1)^2\\\\y=-6(x-1)^2-2[/tex]
Since vertex form is [tex]y=a(x-h)^2+k[/tex], we identify the vertex to be [tex](h,k)\rightarrow(1,-2)[/tex] and the axis of symmetry to be [tex]x=h\rightarrow x=1[/tex]. The y-intercept can be found by setting [tex]x=0[/tex] and evaluating:
[tex]y=-6(x-1)^2-2\\\\y=-6(0-1)^2-2\\\\y=-6(-1)^2-2\\\\y=-6(1)-2\\\\y=-6-2\\\\y=-8[/tex]
Hence, the y-intercept of the parabola is [tex]y=-8[/tex], or [tex](0,-8)[/tex] as an ordered pair.